Enhanced sludge stabilization coupled with microbial fuel cells (MFCs) - Ayol, Azize; Biryol, Idris; Hasar, Halil; Taskan, Ergin (Pergamon-Elsevier Science Ltd, 2021)
This study presents research results on electricity production from waste activated sludge using MFCs during stabilization process. Different MFC configurations equipped with various electrodes were used. Voltage measurements were continuously done during 35 days of MFC operation. Experimental results showed that bioelectricity generation was linked to volatile solids (VS) and protein reductions as a fraction of extracellular polymeric substances (EPS). Double chamber MFC reactor equipped with graphite electrodes had better power and current densities as 312.98 mW/m(2) and 39.07 mu A/cm(2) while single chamber MFC equipped with titanium electrodes revealed better power and current densities as 97.60 mW/m(2) and 17.63 mu A/cm(2), respectively. Molecular results indicated that power outputs of MFCs effected by diverse microbial communities in anode biofilms. Although organic matter degradation is reported as 35%-55% VS reduction for digesters, this research provided a promising approach for sludge stabilization with enhanced degrading of organic matters up to 75% by using MFCs. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Waste activated sludge; Energy harvesting; Microbial fuel cell (MFC); Sludge stabilization; Microbial community; Extracellular polymeric substances